2022
DOI: 10.3389/fgene.2022.823241
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Non-Canonical Nucleic Acid Structures in Organismal Development and Adaptation to Stress Conditions

Abstract: Over the last decades, numerous examples have involved nuclear non-coding RNAs (ncRNAs) in the regulation of gene expression. ncRNAs can interact with the genome by forming non-canonical nucleic acid structures such as R-loops or DNA:RNA triplexes. They bind chromatin and DNA modifiers and transcription factors and favor or prevent their targeting to specific DNA sequences and regulate gene expression of diverse genes. We review the function of these non-canonical nucleic acid structures in regulating gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 138 publications
(197 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that DNA-RNA triplex, a non-canonical nucleic acid structures, participates in the transcriptional activation through recruiting transcription factors, 27 among which hnRNPA2B1 has been previously reported to involve in H3K4 trimethylation (H3K4me3) at target genes to further activate their transcription. 13 , 28 Therefore, we sought to examine whether circTLCD4-RWDD3 activated UBC9 transcription by directly interacting with UBC9 promoter to recruit hnRNPA2B1 and induce the H3K4me3 on UBC9 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that DNA-RNA triplex, a non-canonical nucleic acid structures, participates in the transcriptional activation through recruiting transcription factors, 27 among which hnRNPA2B1 has been previously reported to involve in H3K4 trimethylation (H3K4me3) at target genes to further activate their transcription. 13 , 28 Therefore, we sought to examine whether circTLCD4-RWDD3 activated UBC9 transcription by directly interacting with UBC9 promoter to recruit hnRNPA2B1 and induce the H3K4me3 on UBC9 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, not only was LINC01137 confirmed to co-express with ZC3H12A (r > 0.5; FDR <0.05; certifying their co-regulation under the divergent promoter), but it also forms the RNA–DNA triple helix (also known as triplex) in the genomic location of WWOX using 14 TFOs [typically, TFOs are 12–28 in length ( Li et al, 2022 )]. Such structures can repress or induce gene expression ( Alecki and Vera, 2022 ; Cecconello et al, 2022 ; Warwick et al, 2023 ), but the latter can be assumed in our case. The module evaluating triple helices also returned one TFO within the ZC3H12A gene, which should be noted for future studies.…”
Section: Resultsmentioning
confidence: 99%